2011
DOI: 10.1002/rcm.4715
|View full text |Cite
|
Sign up to set email alerts
|

Effect of elevated CO2 on carbon partitioning in young Quercus ilex L. during resprouting

Abstract: Stored carbon (C) represents a very important C pool with residence times of years to decades in tree organic matter. With the objective of understanding C assimilation, partitioning and remobilization in 2‐year‐old Quercus ilex L., those trees were exposed for 7 months to different [CO2] (elevated: 700 µmol mol−1; and ambient: 350 µmol mol−1 CO2). The 13C‐isotopic composition of the ambient CO2 (ca. −12.8‰) was modified (to ca. −19.2‰) under the elevated CO2 conditions in order to analyze C allocation and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 68 publications
(139 reference statements)
0
2
0
Order By: Relevance
“…Instead, the source of C remobilization varied among species. An increase in the C remobilization has been demonstrated in young Quercus ilex L. and was mostly derived from roots (Aranjuelo et al 2011b).…”
Section: Elevated Co 2 Enhances the C Supply For New Leaf Growth And mentioning
confidence: 95%
“…Instead, the source of C remobilization varied among species. An increase in the C remobilization has been demonstrated in young Quercus ilex L. and was mostly derived from roots (Aranjuelo et al 2011b).…”
Section: Elevated Co 2 Enhances the C Supply For New Leaf Growth And mentioning
confidence: 95%
“…Hence, there appears to be a strong coupling of climate responses in carbon and nitrogen cycling at this temperate heath ecosystem. Aranjuelo et al (paper not presented at the meeting) reported on the finding that, despite having a new C sink, the responsiveness of young Quercus ilex L. resprouts under elevated [CO 2 ] conditions will be strongly conditioned by the plant's capacity to use the extra C present in leaves through its allocation to other organs (roots) and processes (respiration). Gómez‐Muñoz et al determined the gross and net rates of nitrogen mineralisation in soil amended with composted olive mill pomace (COMP; a waste product from the olive oil industry).…”
mentioning
confidence: 99%